The Effect of European Accession Prospects on Foreign Direct Investment Flows - Hakan Güngör; Ayla Ogus Binatli (Izmir University of Economics, Department of Economics, 2010)
The amount of FDI is increasing than any other international transactions during the last two decades. While countries remove barriers and implement policies to attract FDI inflows, the volume of foreign trade and investment increased .The objective of this paper is to enlighten the impact of EU accession of CEEC countries and Turkey on FDI flows into these countries. We perform Arrenalo-Bond - GMM model for the period of 1990-2009 for Poland, Hungary, Czech Republic, Estonia, Slovakia, Romania, Bulgaria, Turkey Croatia, Macedonia, and Ukraine. The empirical results suggest that as agglomeration effects and trade openness are significant determinants of MNCs' activity during the period, traditional determinants, risk factors, labor cost, and market size are insignificant. In addition, the effect of EU accession prospects is found to be positive and significant.
Keywords: F23; 330; European Union; FDI; Turkey; Accession; Candidacy; EU-Mitgliedschaft; Mitgliedschaft; Eurozone; Auslandsinvestition; Osteuropa; Südosteuropa